Multifocal ectopic purkinje-related premature contractions and related cardiomyopathy - Calloe, Kirstine; Magnusson, Helena B. D.; Lildballe, Dorte Launholt; Christiansen, Morten Krogh; Jensen, Henrik Kjærulf (Frontiers in Cardiovascular Medicine, 2023)
In the past 20 years, genetic variants in SCN5A encoding the cardiac voltage-gated sodium channel Nav1.5 have been linked to a range of inherited cardiac arrhythmias: variants resulting in loss-of-function of Nav1.5 have been linked to sick sinus syndrome, atrial stand still, atrial fibrillation (AF) impaired pulse generation, progressive and non-progressive conduction defects, the Brugada Syndrome (BrS), and sudden cardiac death. SCN5A variants causing increased sodium current during the plateau phase of the cardiac action potential is associated with Long QT Syndrome type 3 (LQTS3), Torsade de Pointes ventricular tachycardia and SCD. Recently, gain-of-function variants have been linked to complex electrical phenotypes, such as the Multifocal Ectopic Purkinje-related Premature Contractions (MEPPC) syndrome. MEPPC is a rare condition characterized by a high burden of premature atrial contractions (PACs) and/or premature ventricular contractions (PVCs) often accompanied by dilated cardiomyopathy (DCM). MEPPC is inherited in an autosomal dominant fashion with an almost complete penetrance. The onset is often in childhood. The link between SCN5A variants, MEPPC and DCM is currently not well understood, but amino acid substitutions resulting in gain-of-function of Nav1.5 or introduction of gating pore currents potentially play an important role. DCM patients with a MEPPC phenotype respond relatively poorly to standard heart failure medical therapy and catheter ablation as the PVCs originate from all parts of the fascicular Purkinje fiber network. Class 1c sodium channel inhibitors, notably flecainide, have a remarkable positive effect on the ectopic burden and the associated cardiomyopathy. This highlights the importance of genetic screening of DCM patients to identify patients with SCN5A variants associated with MEPPC. Here we review the MEPPC phenotype, MEPPC-SCN5A associated variants, and pathogenesis as well as treatment options.